Legal implications of regional integration initiatives on special economic zones in Kenya - OluSoyeju, Olufemi Olugbemiga (University of Pretoria, 2017)
Kenya has recently passed a Special Economic Zones law with the aim of providing a legal framework to enable the establishment of Special Economic Zones (SEZs) in the country. Given that the country is also an active member of several regional integration initiatives (of which the study focuses on the East African Community (EAC) in which Kenya is an integral member), this study investigates the legal framework governing SEZs at the national level and the regional level with a view to determine if there is any legal conflict between the two frameworks that may pose a challenge for Kenya in her decision to simultaneously pursue regional integration initiatives and Special Economic Zones development as trade and investment tools. In finding that there is no synergy between the regional integration arrangements in the EAC and SEZ programmes in member countries, this study makes a number of recommendations including that the region should harmonize the regulatory, incentives and strategic structures of SEZ programmes in the member countries.